Co-pyrolysis of municipal solid waste (MSW) and biomass with Co/sludge fly ash catalyst. (15th August 2022) - Gao, Ningbo; Humphrey Milandile, Mwenya; Tariq Sipra, Ayesha; Su, Sheng; Miskolczi, Norbert; Quan, Cui
Highlights: Copyrolysis of municipal solid waste (MSW) and biomass improved product yield. Catalytic copyrolysis under sludge fly ash-based catalyst enhanced syngas production. Concentration of complex liquid compounds and heavy hydrocarbons was minimized. Combined catalytic effect of metal elements in fly ash improve pyrolysis performance. Abstract: Catalytic co-pyrolysis of municipal solid waste (MSW) and biomass pine sawdust (PSD) under sludge fly ash (SFA) could be a breakthrough towards the energy challenges and waste management. This paper aims to develop a unique cobalt-alkali-SFA (Co-A-SFA) catalyst, in order to investigate its influence under optimal operating conditions in a fixed bed reactor for syngas production. The catalytic activity was assessed under different Co loading and support ratios. The results indicated that in the presence of Co-A-SFA catalyst, gas production increased due to alkali pretreated fly ash catalyst. Moreover, increasing the Co loading from 5 wt% to 10 wt%, the syngas production increased irrespective of the individual feedstock ratios. Under catalytic conditions of 5 and 10 wt% the H2 yield to 25.4% and 28.3% for 50/50 MSW/PSD compared to 11.5 wt% under no catalyst. Catalytic co-pyrolysis of MSW and PSD also minimized the concentration of complex liquid compounds and heavy hydrocarbons. Therefore, this study establishes a new approach towards energy production and sustainable waste management through useful resource utilization of MSW, PSD and SFA. The outcomes acquired in this investigation showed that blended feedstock in co-pyrolysis of MSW and pine sawdust could enhance production of valuable syngas under SFA-based catalyst.